A DFT Study on Theoretical Investigation of Application of Combining Pristine C60 and doped C60 with Silicon and Germanium Atoms for Solar cells - Leila Hojatkashani (Challenges and Advances in Chemical Science Vol. 3, 2021)
Solar energy and its conversion to electricity is an important research in the last decade. Solar cells are consist of a p-type semiconductor as donor and an n-type semiconductor as acceptor. Organic polymers as organic semiconductors are used in an organic solar cell. This research is a theoretical investigation of Fullerene C60 as donor and C60 doped derivatives with Silicon and Germanium atoms as acceptors for basic structure of a solar cell. This research is done not only with using related equations but also with investigating theoretical UV-VIS spectrum of the chosen donors-acceptors and their absorption wavelengths, oscillator strength and maximum coefficient absorptions of these solar cells.